2021
DOI: 10.3390/microorganisms9081775
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pan-Genome Analysis of Oral Veillonella Species

Abstract: The genus Veillonella is a common and abundant member of the oral microbiome. It includes eight species, V. atypica, V. denticariosi, V. dispar, V. infantium, V. nakazawae, V. parvula, V. rogosae and V. tobetusensis. They possess important metabolic pathways that utilize lactate as an energy source. However, the overall metabolome of these species has not been studied. To further understand the metabolic framework of Veillonella in the human oral microbiome, we conducted a comparative pan-genome analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The abundance of Bacteroides fragilis ( p = 0.0009) and Veillonella parvula ( p = 0.01) was markedly enriched in CRC patients. Notably, Veillonella parvula is a common and abundant member of the oral microbiome and possesses important metabolic pathways that utilize lactate as an energy source ( Mashima et al, 2021 ), but there have been no previous reports that this bacterium was enriched in CRC patients. Some bacteria with probiotic properties, such as Blautia , Eubacterium rectale ATCC33656, Lachnospiraceae , and Eubacterium hallii , were significantly enriched in NC controls ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of Bacteroides fragilis ( p = 0.0009) and Veillonella parvula ( p = 0.01) was markedly enriched in CRC patients. Notably, Veillonella parvula is a common and abundant member of the oral microbiome and possesses important metabolic pathways that utilize lactate as an energy source ( Mashima et al, 2021 ), but there have been no previous reports that this bacterium was enriched in CRC patients. Some bacteria with probiotic properties, such as Blautia , Eubacterium rectale ATCC33656, Lachnospiraceae , and Eubacterium hallii , were significantly enriched in NC controls ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the possible classification of other enterotypes, Liang et al (2017) found that Enterobacteriaceae could be a new subtype of enterotypes in the Asian population. In a study based on a Chinese population, Lu et al (2021) identified four enterotypes in 2678 healthy Chinese people, three of which were enriched in Prevotella, Bacteroides and Escherichia coli, while the fourth was a mixed type with no dominant genus. In this study, the three enterotypes were consistent with those seen in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella spp. are considered commensal bacteria present in the oral cavity and the gastrointestinal tract of humans, due to being part of the core microbiome [ 49 , 50 ]. They are known to be involved in cross-feeding and co-aggregation with acidogenic species in other environments [ 51 ], using their metabolic intermediates, which suggest that they act as an acid sink.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the identification of these virulence factors and a more detailed molecular and functional characterisation of Veillonella in caries-associated biofilms, in combination with a more thorough characterisation of other microorganisms, could be the key for the development of strategies to modulate the microbiota by using pre or probiotics. A more recent molecular characterisation of oral Veillonella revealed that the genomes of oral Veillonella species were remarkably diverse, and that these Veillonella have conserved pathways that utilise carbohydrates other than lactate as an energy source [ 50 ], which might be an interesting finding of their potential pathogenic traits as oral species. Furthermore, RNA sequencing seems to show higher abundances of Veillonella than DNA sequencing.…”
Section: Discussionmentioning
confidence: 99%